2022
DOI: 10.3389/fgene.2022.947551
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis-Related lncRNAs are Biomarkers of Prognosis and Immune Microenvironment in Head and Neck Squamous Cell Carcinoma

Abstract: Background: Cuproptosis is a new type of cell death that induces protein toxic stress and eventually leads to cell death. Hence, regulating cuproptosis in tumor cells is a new therapeutic approach. However, studies on cuproptosis-related long noncoding RNA (lncRNA) in head and neck squamous cell carcinoma (HNSC) have not been found. This study aimed to explore the cuproptosis-related lncRNAs prognostic marker and their relationship to immune microenvironment in HNSC by using bioinformatics methods.Methods: RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…Actually, many studies had reported that cuproptosis-related lncRNA signature could serve as a prognostic biomarker in many types of cancer. Liu et al constructed cuproptosis-related lncRNAs as biomarkers of prognosis and the immune microenvironment in squamous cell carcinoma (39). Another cuproptosis-related lncRNA signature could guide the prognosis and immune microenvironment in osteosarcoma (40).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, many studies had reported that cuproptosis-related lncRNA signature could serve as a prognostic biomarker in many types of cancer. Liu et al constructed cuproptosis-related lncRNAs as biomarkers of prognosis and the immune microenvironment in squamous cell carcinoma (39). Another cuproptosis-related lncRNA signature could guide the prognosis and immune microenvironment in osteosarcoma (40).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical information was gathered, including TNM stage, pathological grade, age, gender, follow-up period, and survival status. In this study, 22 genes associated with cuproptosis were chosen for examination based on previously published studies [7][8][9][10] .…”
Section: Data Collectionmentioning
confidence: 99%
“…Copper chelators and copper ionophores have excellent anticancer activity, as well as copper coordination compounds have also made great progress in cancer therapy, so copper-targeted anticancer drugs have broad application prospects (10). Recently, studies of cuproptosis-related genes as potential biomarkers in tumors have been confirmed in many other cancers, such as skin cutaneous melanoma (SKCM) (11), clear cell renal cell carcinoma (ccRCC) (12), bladder cancer (BLCA) (13), triplenegative breast cancer (TNBC) (14), lung cancer (15), and head and neck squamous cell carcinoma (HNSC) (16).…”
Section: Introductionmentioning
confidence: 99%